Clinical Practice at the Edge of Care Developments in Working with At-Risk Children and their Families - Smith, Laura (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book brings together psychological and psychotherapeutic contributions in clinical practice with at-risk children and their families Chapters by experts working in a range of edge-of-care settings give an essential account of real-world clinical challenges and dilemmas; whilst drawing on relevant theory and the growing evidence base for edge of care work with children and families. This title will be of interest to both clinical and social work practitioners, those commissioning and developing best practice in edge of care services, scholars and students of Clinical Psychology, Systemic Psychotherapy and related disciplines.